IMPACT OF SHOPPING MALLS SERVICES ON CUSTOMERS SATISFACTION IN CHENNAI CITY - Vinotha, Dr.M.Gurupandi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Shopping is an integral part of life for an every individual. With the change in the living style of the people, they prefer to buy from a place where they can buy everything under one roof. Economic development and the change in consumer culture, shopping malls in India have impressive growth and replaced the traditional departmental store and retail outlet. It has collection of shops and restaurants and entertainment facilities. Satisfaction and loyalty such as perceived value and service quality were not analyzed in this research. The purpose of the study impact of shopping malls services on customers satisfaction. The main objectives of the study the impact factor with level of satisfaction of the customers.The study comprises both primary and secondary data. Primary data collected from customer through the questionnaire method, the sample size is 360. A convenient sampling method was used for the study. The concluded of the study Customer services about children, informative customer services on satisfaction and loyalty, shopping Centre management should not ignore these types of services since they are really important.